As Value-based Economics, How Does Islamic Economics deal with Scientific Method in Disruptive Era of Digitalization? - Herman, Sebastian (MALIA: Jurnal Ekonomi Islam, 2026)
Purpose: This study aims to analyze philosophically how Islamic economics, as a value-based system, engages with the mainstream scientific method. Design/Methodology/Approach: This research uses a qualitative approach through literature review and content analysis of economic, philosophical, and Islamic economic sources. Findings: The study finds that Islamic economics may employ scientific methods and analytical tools as long as they do not conflict with the Islamic worldview. These methods function as instruments to observe human behavior as an expression of free will granted by Allah. Practical Implications: Islamic economists can adopt empirical methods selectively to strengthen the relevance and practical development of Islamic economics without compromising its ethical foundations. Originality/Value: This study provides a philosophical justification for integrating scientific methods within Islamic economics as a value-based discipline.